2018
DOI: 10.1177/0267659118778170
|View full text |Cite
|
Sign up to set email alerts
|

Central ECMO for circulatory failure following pediatric liver transplantation

Abstract: We describe the case of a 4-year-old male with a past medical history significant for nephrotic syndrome, short-bowel syndrome and fulminant hepatic failure status post (s/p) liver transplant (LT) who developed early post-transplant allograft dysfunction (hyperbilirubinemia, coagulopathy) and septic shock requiring central extracorporeal membrane oxygenation (ECMO). He remained on ECMO for 85 hours before he was decannulated without event and later underwent repeat LT. This case highlights the potential of cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In 3 pediatric liver recipients, they developed graft failure and pulmonary failure after the first LT, supported by ECMO for a few days, and got retransplantation. [ 12 , 14 , 15 ] Only 1 patient who suffered from acute respiratory distress syndrome clearly underwent ECMO before LT (13 days). [ 16 ] Our case is the first case using ECMO as a measure to prevent cardiocirculatory failure in LT.…”
Section: Discussionmentioning
confidence: 99%
“…In 3 pediatric liver recipients, they developed graft failure and pulmonary failure after the first LT, supported by ECMO for a few days, and got retransplantation. [ 12 , 14 , 15 ] Only 1 patient who suffered from acute respiratory distress syndrome clearly underwent ECMO before LT (13 days). [ 16 ] Our case is the first case using ECMO as a measure to prevent cardiocirculatory failure in LT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in 2018, Scott et al [42] also reported on a pediatric case. Specifically, after undergoing a liver transplant, the pediatric patient developed post-transplant liver dysfunction (hyperbilirubinemia and coagulation dysfunction) and RSS.…”
Section: Application Of Ecmo To the Treatment Of Rss Post-transplant ...mentioning
confidence: 99%
“…From 24 articles initially identified as potentially eligible, 16 studies were retrieved for data extraction after fulltext review (Figure 2). The studies included in the present systematic review were published between 2000 and 2020 and were conducted in the United States (n = 7), 8,9,[18][19][20][21][22] Asia (n = 5), 7,12,[23][24][25] Europe (n = 3), [4][5][6] and Canada (n = 1). 26 A total of 22 children that received ECMO on the day of transplant or later were included in the systematic review (Table 4).…”
Section: Systematic Review Of the Literaturementioning
confidence: 99%